Evaluating the Relationship Between Modernization and Productivity in Udayapur Cement Industry: A Diagnostic and Exploratory Study (The Harvest, 2026)
This study examines how modernization relates to productivity at Udayapur Cement Industries Ltd. (UCIL), a state-owned producer operating well below installed capacity. The purpose is to diagnose organizational and technical bottlenecks and explain how modernization shortfalls translate into measurable productivity losses. Using a diagnostic, exploratory design, the study applies qualitative document analysis to an internal UCIL report. Texts were thematically coded into modernization dimensions automation and process control, energy efficiency, workforce capability, digital integration, and administrative enablers and mapped against productivity outcomes: output levels, operational efficiency, cost structure, downtime profile, and competitiveness. Findings indicate pervasive modernization gaps: legacy machinery and limited real-time control; manual quality control without online analytics; a predominantly reactive maintenance regime lacking predictive tools; unreliable grid power with diesel dependence and no Variable Frequency Drives or Waste Heat Recovery; workforce skill deficits and aging profiles; fragmented information systems without an Enterprise Resource Planning backbone; and bureaucratic procurement with constrained financial autonomy. These conditions are consistently associated with under-utilized capacity, unstable operations, elevated unit energy and operating costs, frequent unplanned downtime, and weakened market competitiveness. The results point to a phased pathway: establish plant-wide control and online quality analytics, shift to predictive maintenance with sensor enabled monitoring and a Computerized Maintenance Management System, reduce energy intensity via targeted retrofits, deploy ERP and basic dispatch tracking, and embed targeted upskilling to secure adoption.